Global Distribution of Electrostatic Electron Cyclotron Harmonic Waves in Saturn's Magnetosphere: A Survey of Over‐13‐Year Cassini RPWS Observations. Issue 4 (16th April 2021) - Long, Minyi; Gu, Xudong; Ni, Binbin; Cao, Xing; Ma, Xin; Zhao, Yiwen
Abstract: Based on the measurements from Radio and Plasma Wave Science instrument onboard the Cassini spacecraft over 13 years, we perform a statistical analysis of electron cyclotron harmonic (ECH) wave spatial distribution in Saturn's magnetosphere. The wave occurrence rates, amplitudes, and peak frequencies as functions of magnetic local time, L ‐shell, and magnetic latitude are investigated in detail. Our results confirm that the fundamental band ECH waves mainly occur near the magnetic equator (| λ | < 5°) and also at high latitudes (20° < | λ | ≤ 40°), with averaged amplitudes of about 0.01–0.1 mV/m. By comparison, the amplitudes and occurrence rates of higher harmonics n decrease significantly, and the higher harmonic bands tend to occur at lower L ‐shells along with the enhanced day‐night asymmetry. Overall, Saturnian ECH emissions are preferentially a nightside phenomenon and exhibit a gap in the midlatitude regions (5° < | λ | ≤ 20°) for the occurrence rates. The occurrence rates of ECH waves are higher at high latitudes than those near the magnetic equator, but the statistically averaged amplitudes of high latitude emissions are relatively weaker. Furthermore, the averaged peak frequencies of each ECH wave harmonic band are generally below ( n + 1/2) f ce and have the smallest deviation from ( n + 1/2) f ce near the equator. These results can be readily adopted as representative inputs to quantify the electron scattering effect of multi‐harmonic Saturnian ECH waves and investigate the underlying contribution of ECH emissions to the evolution of the Saturnian radiation belt. Plain Language Summary: Similar to Earth, Saturn possesses a strong internal magnetic field, which reacts to the solar wind flows to form the magnetosphere. There are a variety of plasma waves in Saturn's magnetosphere, which can either accelerate or decelerate energetic electrons via wave‐particle interaction processes. As an electrostatic wave mode frequently observed in Saturn's magnetosphere, electron cyclotron harmonic (ECH) waves near the half‐integral harmonics of electron cyclotron frequency, that is, ( n + 0.5) f ce ( n = 1, 2, 3), remain rather limitedly understood in the morphological characteristics, including their occurrence pattern, wave amplitudes and frequency spectra. Based on long‐term wave data over 13 years from the Cassini spacecraft, we investigate comprehensively the global distribution properties of Saturian ECH waves within ∼ 5–10 R s, which are essential to quantify the particular role of ECH waves in the energetic electron dynamics in the Saturnian magnetosphere. Our results clearly indicate that Saturnian ECH waves are more likely to be a nightside phenomenon and occur more frequently at high latitudes than the equatorial regions, while the high‐latitude wave amplitudes are statistically weaker. It is also revealed that in statistics the peak wave frequencies of Saturian ECH emissions are generally below ( n + 1/2) f ce, with the smallest deviation from ( n + 1/2) f ce in the near‐equatorial regions. Key Points: The averaged amplitudes of Saturnian electron cyclotron harmonic (ECH) waves have a pronounced magnetic local time asymmetry, and they are larger on the nightside than the dayside The ECH wave occurrence rates are higher at high latitudes than those near the equator, but high‐latitude averaged amplitudes are weaker The ECH wave averaged peak frequencies are generally below ( n + 1/2) f ce, with the smallest deviation from ( n + 1/2) f ce near the equator